Amino acid metabolic signaling influences Aedes aegypti midgut microbiome variability. - Sarah M Short; Emmanuel F Mongodin; Hannah J MacLeod; Octavio A C Talyuli; George Dimopoulos (Public Library of Science (PLoS), 2017)
The mosquito midgut microbiota has been shown to influence vector competence for multiple human pathogens. The microbiota is highly variable in the field, and the sources of this variability are not well understood, which limits our ability to understand or predict its effects on pathogen transmission. In this work, we report significant variation in female adult midgut bacterial load between strains of A. aegypti which vary in their susceptibility to dengue virus. Composition of the midgut microbiome was similar overall between the strains, with 81-92% of reads coming from the same five bacterial families, though we did detect differences in the presence of some bacterial families including Flavobacteriaceae and Entobacteriaceae. We conducted transcriptomic analysis on the two mosquito strains that showed the greatest difference in bacterial load, and found that they differ in transcript abundance of many genes implicated in amino acid metabolism, in particular the branched chain amino acid degradation pathway. We then silenced this pathway by targeting multiple genes using RNA interference, which resulted in strain-specific bacterial proliferation, thereby eliminating the difference in midgut bacterial load between the strains. This suggests that the branched chain amino acid (BCAA) degradation pathway controls midgut bacterial load, though the mechanism underlying this remains unclear. Overall, our results indicate that amino acid metabolism can act to influence the midgut microbiota. Moreover, they suggest that genetic or physiological variation in BCAA degradation pathway activity may in part explain midgut microbiota variation in the field.